Editorial: Device-to-Device Communication in 5G Networks; Mobile Networks and Applications; Vol. 22 - Bisvas S. K. Sanzhay Kumar; Ziviani A. Artur; Jain R. Raj; Lin J. Jiachin; Rodrigues J. J. P. C. Joel (2017, 2017)
Title screen